Mothers' Resilience: Experiences of Intimate Partner Violence Survivors at Work - Kathryn Showalter; Kathryn Maguire-Jack; Rebecca McCloskey (MDPI AG, 2022)
Mothers who experience intimate partner violence can be resilient in maintaining employment during periods of abuse. The current qualitative study examines mothers' experiences of abusive workplace disruptions as well as helpful responses from workplaces. Two main research questions are addressed: 1. What ways do abusive partners use issues related to children to disrupt mothers' employment? 2. How do workplaces respond to mothers experiencing IPV? How do mothers show resilience? Mothers (n = 18) receiving services for abuse explained that abusive partners disrupted their work through compromising or withholding childcare, manipulating them through children, and jeopardizing child safety during work hours. However, mothers showed resilience when coworkers extend housing, childcare, and genuine concern for their situations. Implications for researchers, practitioners, and employers of survivors are discussed.